The Influence of Foreign Investment and Domestic Investment on Indonesian Economic Growth - Lelin Jannatunisa; Sutrisno Sutrisno; Ratna Fitri Astuti; Ruspian Ruspian (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2025)
Indonesia's success is greatly influenced by economic growth, which is driven by a number of important elements such as exports, investment, consumption, and government involvement in infrastructure development. Determining the partial and simultaneous effects of foreign and domestic investment on Indonesia's economic growth is the purpose of this study. The type of research used is explanatory research with a quantitative approach. All data on foreign investment, domestic investment, and Indonesia's economic growth are the population in this study. The sample in this study consists of time series data from the Central Statistics Agency and Databox for the last ten years, from 2013 to 2023, on foreign investment, domestic investment, and Indonesia's economic growth. Data analysis techniques used in this study include documentation techniques, multiple linear regression tests, classical assumption tests (such as normality, multicollinearity, and heteroscedasticity tests, and autocorrelation), hypothesis tests (such as t and f tests), and determination coefficient tests (R2). Data analysis using eviews version 12.